COMPREHENSIVE ASSESSMENT OF CEPHALOMETRIC PARAMETERS IN PATIENTS WITH VARIOUS FORMS OF DISTAL OCCLUSION, DEPENDING ON THE TYPE OF HEIGHT/FACE (American Journal of Research in Humanities and Social Sciences, 2024)
The incidence of distal occlusion among anomalies of the maxillofacial region is increasing due to many endogenous and exogenous factors. According to various researchers, the distal ratio of the jaw bones may be due to the predominance of the growth of the upper, the lag in the growth of the lower, or due to problems of both jaws [5; pp. 67-84]. An approximately equal ratio of jaw bone growth types was determined in Zinchenko A.Yu. (2003) [4; pp. 57-88] with distal occlusion: in 36% of patients, neutral, 33% and 31% of the examined patients had horizontal and vertical types, respectively. E. J. Vares (1969) established that the jaws normally have a downward and anterior growth direction at an angle of about 50° to the base of the skull (NS). Depending on the growth trend, the anomaly may worsen or its clinical picture may self-regulate due to the growth of the maxillary system. Orthodontics specialists are changing their views on the treatment of distal occlusion, taking into account the component of jaw growth and its relationship with sagittal malocclusion [3; p. 38; 4; p.56; 6; p.102; 7; p.165; 10; p.102-104].